Nanoscale mapping of shifts in dark plasmon modes in sub 10 nm aluminum nanoantennas. (19th November 2022) - Elibol, Kenan; Downing, Clive; Hobbs, Richard G
Abstract: In this work, we report the fabrication and spectroscopic characterization of subwavelength aluminum nanocavities—consisting of hexamer or tetramer clusters of sub 10 nm width Al nanorods—with tunable localized surface plasmon resonance (LSPR) energies on suspended SiN x membranes. Here the volume plasmon (VP) and LSPR modes of lithographically-fabricated Al nanocavities are revealed by low-loss electron energy-loss spectroscopy (EELS) in an aberration corrected scanning transmission electron microscope (STEM). We show that the existence of grain boundaries (GBs) in these nanocavities results in shifts in the VP energy and a reduction in the VP lifetime. We map the VP energy and lifetime across GBs and we observe a decrease in VP energy and lifetime at GBs that is consistent with a reduction in free carrier density and increased plasmon scattering at these locations. Dipolar LSPR modes resonant in the UV and blue regions of the electromagnetic spectrum as well as higher-energy optically dark quadrupolar and hexapolar LSPR modes are also observed and mapped by STEM and EELS. All LSPR modes are confirmed via electromagnetic simulations based on the boundary element method. Both tetramer and hexamer structures support the excitation of dipolar bright and dipolar dark modes. Finally, we find that asymmetries in fabricated nanorod hexamer and tetramer nanocavities result in a mode mixing leading to a shift in dipolar dark LSPR modes.